ANALISIS ANTRIAN PENGUNJUNG DAN KINERJA SISTEM DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Astrelita, Fahra Pracendi; Sugito, Sugito; Wuryandari, Triastuti (Jurnal Gaussian, 2015)
Department of Population and Civil Registration (Dispendukcapil) has the duty of assistance in the field of population and civil registration. Civil registration services such as services related to birth, death, marriage, and divorce. As a service provider, Dispendukcapil of Semarang has the motto "No Day Without Service Quality Improvement". Queuing problem is that often occur and must be considered. The queue situation occurs because the number of visitors to a service facility exceeds the available capacity to perform such services. A system is always trying to serve visitors well in accordance with the rate of arrival of each visitor. Therefore please note the size of the system's performance on each section on service system. Dispendukcapil queuing system at Semarang city located on the Legalized, Change Data, Birth, Death, Divorce/Marriage, and Decision Act. Based on the results obtained and the analysis of models of queuing at the counter is Legalized (G/G/2):(GD/∞/∞), while the counter is Birth (G/G/3):(GD/∞/∞), the Change the counter Data, Death, Divorce / Marriage is (M/G/1):(GD/∞/∞) and Decision Deed is (G/G/1):(GD/∞/∞).  Keywords: Queuing System, Dispendukcapil, Dispendukcapil of Semarang, Legalized, Birth, Death, Divorce, Marriage.